2010
DOI: 10.1590/s1516-35982010000800019
|View full text |Cite
|
Sign up to set email alerts
|

Oregano essential oil as food additive for piglets: antimicrobial and antioxidant potential

Abstract: -This study aimed to investigate the effect of dietary supplementation of oregano essential oil on the performance and on the occurrence of diarrhea in weanling pigs, as well as its antioxidant and antimicrobial activity evaluated in vitro. It was compared four treatments (diets): negative control; positive control, 0.5% ZnO (preventive diarrhea) + 0.05% zinc acitracin (growth promoter); or 0.003% of essential oil of oregano, combined or not with preventive of diarrhea.Weight gain, feed intake and feed convers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…In this study, the addition of phytobiotics reduced the concentration of protein carbonyl in the plasma of pigs during the nursery and growing period. These results confirmed the antioxidant properties of oregano-based phytobiotics, as previously reported [ 32 , 35 , 42 ]. According to Zou et al [ 32 ], oregano essential oil diminished the oxidative stress in IPEC-J2 cells by inducing the expression of superoxide dismutase (SOD1) and glutathione through the activation of nuclear-factor-erythroid-2-related factor-2 (Nrf2), which can be one of the anti-oxidant modes of action of oregano-based phytobiotics.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the addition of phytobiotics reduced the concentration of protein carbonyl in the plasma of pigs during the nursery and growing period. These results confirmed the antioxidant properties of oregano-based phytobiotics, as previously reported [ 32 , 35 , 42 ]. According to Zou et al [ 32 ], oregano essential oil diminished the oxidative stress in IPEC-J2 cells by inducing the expression of superoxide dismutase (SOD1) and glutathione through the activation of nuclear-factor-erythroid-2-related factor-2 (Nrf2), which can be one of the anti-oxidant modes of action of oregano-based phytobiotics.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have been conducted using OEO, alone or mixed with other spices and plants, to supplement the diet of weaning pigs and finishing birds, or to use it as an ingredient in meat products to add or enhance functional properties. The results are inconsistent, possibly caused by the origin of the essential oils or herb species, the quantity added to the feed, or the environmental conditions used in the trial, to name a few (Henn et al 2010;Zeng et al 2015). But probably one of the most important factors is the content of carvacrol in the essential oils used as it differs between oregano species (Teixeira et al 2013;Mechergui et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…(2009) testified the antimicrobial effects of carvacrol and thymol isolated from oregano on many kinds of bacteria including Escherichia coli, Staphylococcus aureus and Streptococcus mutans in vitro. Furthermore, another experiment showed that OEO had inhibited the oxidant of fatty acids except for antimicrobial activity on Escherichia coli, Salmonella typhimurium and Clostridium perfringens ( Henn et al., 2010 ).…”
Section: Introductionmentioning
confidence: 99%